A INDÚSTRIA DE CALÇADOS DE FORTALEZA - Ary, Antônio Jereissate; Souza, Edivaldo Tavares de; Gomes, Francisco de Assis Lima; Gonçalves Filho, Geraldo W.; Leitão, José Walder (Revista Econômica do Nordeste, 1987)
ACERVO HISTORICO